Phytochemical Composition and Antioxidant Capacity of Three Malian Medicinal Plant Parts - Muanda, François (Hindawi Publishing Corporation, 2011)
This study evaluates the levels of total polyphenolic compounds in three Malian medicinal plants and determines their antioxidant potential. Quantitative and qualitative analysis of polyphenolics contained in plants extracts were carried out by RP-C18 RP–HPLC using UV detector. The antioxidant activity was determined by three tests. They are phosphomolybdenum, DPPH (2,2-diphenyl-1 picrylhydrazyl) and ABTS [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic)] tests. The total phenolic and the total flavonoid contents varied from 200 to 7600 mg 100 g(−1) dry weight (dw), expressed as gallic acid equivalents and from 680 to 12 300 mg 100 g(−1) dw expressed as catechin equivalents, respectively. The total anthocyanin concentrations expressed as cyanin-3-glycoside equivalent varied from 1670 to 28 388 mg 100 g(−1) dw. The antioxidant capacity was measured by determining concentration of a polyphenolic (in mg ml(−1)) required to quench the free radicals by 50% (IC(50)) and expressed as vitamin C equivalent antioxidant capacity. The IC(50) values were ranked between 2.68 and 8.80 μg ml(−1) of a solution of 50% (v/v) methanol in water. The uses of plants are rationalized on the basis of their antioxidant capacity.